Serum bicarbonate and cardiovascular events in hypertensive adults: results from the Systolic Blood Pressure Intervention Trial. Issue 8 (14th August 2019) - Dobre, Mirela; Pajewski, Nicholas M; Beddhu, Srinivasan; Chonchol, Michel; Hostetter, Thomas H; Li, Ping; Rahman, Mahboob; Servilla, Karen; Weiner, Daniel E; Wright, Jackson T; Raphael, Kalani L
Abstract: Background: Low serum bicarbonate level is associated with increased mortality, but its role as a predictor of cardiovascular disease (CVD) is unclear. This study evaluates the association between serum bicarbonate concentration and CVD and whether the effect of intensive blood pressure (BP) lowering on CVD outcomes is modified by serum bicarbonate level. Methods: The Systolic Blood Pressure Intervention Trial (SPRINT) randomized participants to a systolic BP target <120 mmHg (intensive treatment) or <140 mmHg (standard treatment). The primary CVD outcome was a composite of nonfatal myocardial infarction (MI), acute coronary syndrome not resulting in MI, stroke, acute decompensated heart failure and CVD death. Cox proportional hazards models adjusted for demographic, clinical and laboratory characteristics were used to evaluate the association of interest in 9334 SPRINT participants (ClinicalTrials.gov: NCT01206062). Results: Over a median follow-up of 3.33 years (interquartile range 2.87–3.87 years), 618 (6.6%) participants experienced a primary CVD outcome. Participants with serum bicarbonate <22 mEq/L had a significantly higher risk of the primary CVD outcome (hazard ratio 1.54; 95% confidence interval 1.11–2.14, P = 0.01), compared with participants with bicarbonate 22–26 mEq/L. The magnitude of the CVD risk reduction with intensive BP lowering was similar across bicarbonate strata (P-value for interaction = 0.97). Conclusions: In hypertensive individuals, serum bicarbonate level <22 mEq/L was associated with an increased CVD risk. The effect of intensive BP lowering on CVD outcomes was not modified by the serum bicarbonate level.